Expression of somatostatin receptors in normal and cirrhotic human liver and in hepatocellular carcinoma. Issue 8 (9th July 2004) - Reynaert, H; Rombouts, K; Vandermonde, A; Urbain, D; Kumar, U; Bioulac-Sage, P; Pinzani, M; Rosenbaum, J; Geerts, A
Abstract : Background: Somatostatin analogues have been used with conflicting results to treat advanced hepatocellular carcinoma (HCC). The aim of this study was to investigate expression of somatostatin receptor (SSTR) subtypes in human liver, and to examine the effect of selective SSTR agonists on proliferation, apoptosis, and migration of hepatoma cells (HepG2, HuH7) and hepatic stellate cells (HSCs). Methods: Expression of SSTRs in cell lines, normal and cirrhotic liver, and HCC was examined by immunohistochemistry and reverse transcription-polymerase chain reaction. Effects of SSTR agonists on proliferation and apoptosis of tumour cells and HSCs were assessed by the 5-bromo-2′ deoxyuridine and TUNEL methods, respectively. The influence of SSTR agonists on migration was investigated using Boyden chambers. Results: In normal liver, both hepatocytes and HSCs were negative for all five SSTRs. Cirrhotic liver and HCC as well as cultured hepatoma cells and HSCs expressed all five SSTRs, both at the protein and mRNA levels, except for HuH7 cells which did not immunoreact with SSTR3. None of the agonists influenced proliferation or apoptosis. However, compared with untreated cells, L-797, 591, an SSTR1 agonist, reduced migration of HepG2, HuH7, and HSCs significantly to 88 (7)% (p<0.05), 83 (11)% (p<0.05), and 67 (13)% (p<0.01), respectively. Conclusions: Cirrhotic liver and HCC express SSTRs. Although the somatostatin analogues used in this study did not affect proliferation and apoptosis, stimulation of SSTR1 may decrease invasiveness of HCC by reducing migration of hepatoma cells and/or HSCs. Clinical trials evaluating somatostatin analogues for the treatment of HCC should take these findings into account.